A lost decade? A renewed case for adult social care reform in England. (7th April 2021) - GLASBY, JON; ZHANG, YANAN; BENNETT, MATTHEW R.; HALL, PATRICK
Abstract: Drawing on a 2010 analysis of the reform and costs of adult social care commissioned by Downing Street and the UK Department of Health, this paper sets out projected future costs under different reform scenarios, reviews what happened in practice from 2010-19, explores the impact of the growing gap between need and funding, and explores the relationship between future spending and economic growth. In the process, it identifies a 'lost decade' in which policy makers failed to act on the warnings which they received in 2010, draws attention to the disproportionate impact of cuts on older people (compared to services for people of working age) and calls for urgent action before the current system becomes unsustainable.